PARTISIPASI MASYARAKAT KOTA BITUNG DALAM MEWUJUDKAN TERTIB BERLALULINTAS - ROTINSULU, RAHEL; KAUNANG, MARKUS; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract.Achieving good governance requires an active participation from the community. One of the tangible forms ofcommunity participation is in realizing tersb traffic. Bitung City which is an industrial city is faced with theproblem of orderly traffic that requires the participation of the community in its participation in planning,implementation, acceptance and utilization as well as in development evaluation in order to realize the trafficorder. This research is conducted to analyse the cause of the lack of good public participation in realizing theorderly traffic in the effort of scientific development in the study of resource management. By using qualitativeapproach found that the participation of Bitung City community in realizing the orderly traffic has not runwell because so far only the transportation business group and the leader of the organization of the driverinvolved in the planning process, the general public does not have awareness in the implementation of orderlytraffic and in acceptance and utilization Bus stops, ferry terminals and no evaluation of the development of thetransportation sector.Keywords: Participation, Community, Orderly Traffic.